Effects of multidrug-resistant bacteria and multi-antibiotic combination on intestinal microbiota in mice - Ma, Jing; Gong, Zheng; Kang, Meiling; Tian, Zhongjing; You, Liping; Ding, Chengshi (Frontiers in Microbiology, 2025)
Multidrug-resistant bacteria are a clinical and an epidemiological challenge. However, the effects of multidrug-resistant bacteria and multi-antibiotic combination on gut microbiota are unclear. In this study, the effects of multidrug-resistant bacteria and multi-antibiotic combination on intestinal microbiota in mice have been observed by high-throughput sequencing. Resistant Escherichia coli (RP4) and 0.5, 1, and 2 mg/L antibiotics (Amp, Km, and Tet multi-antibiotic combination) could decrease the number of specific operational taxonomic units from 223 in the normal saline control group to 178 in the antibiotic-resistant bacteria group and 34 in the antibiotic group, and antibiotics are the biggest influencing factor. Multidrug-resistant bacteria and multi-antibiotic combination could affect the function of intestinal microbiota, and the effect of multidrug-resistant bacteria was similar to that of multi-antibiotic combination. Small intestine is the main colonization site of antibiotic-resistant bacteria, and Proteobacteria and Bacteroidetes are the major antibiotic-resistance acquired bacteria as determined by transmission electron microscopy and agarose plate screening culture.